2015
DOI: 10.1007/s12021-015-9266-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Intracranial Volume in Brain Research: An Evaluation of Methods

Abstract: Intracranial volume (ICV) is a standard measure often used in morphometric analyses to correct for head size in brain studies. Inaccurate ICV estimation could introduce bias in the outcome. The current study provides a decision aid in defining protocols for ICV estimation across different subject groups in terms of sampling frequencies that can be optimally used on the volumetric MRI data, and type of software most suitable for use in estimating the ICV measure. Four groups of 53 subjects are considered, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…We then related HPC volumes to (1) age and (2) performance on the statistical learning and associative inference tasks as described below. As recent work suggests that FSL may be superior for estimating ICV in pediatric populations (Sargolzaei et al, 2015), we also verified our findings using ICV estimated using tools available through FSL (following the ENIGMA protocol; http://enigma.ini.usc.edu). Adjusting for overall head size using the FSL-based ICV estimates did not substantially change any of our findings (results not reported).…”
Section: Methodssupporting
confidence: 85%
“…We then related HPC volumes to (1) age and (2) performance on the statistical learning and associative inference tasks as described below. As recent work suggests that FSL may be superior for estimating ICV in pediatric populations (Sargolzaei et al, 2015), we also verified our findings using ICV estimated using tools available through FSL (following the ENIGMA protocol; http://enigma.ini.usc.edu). Adjusting for overall head size using the FSL-based ICV estimates did not substantially change any of our findings (results not reported).…”
Section: Methodssupporting
confidence: 85%
“…Here we sought to determine if FD is correlated with ICV, such that we can appropriately control for this relationship, if it exists. We estimated ICV using FreeSurfer (Buckner et al, 2004), which has been shown to correspond well with manual tracing (Sargolzaei et al, 2015). ICV was only weakly related to age differences [ r (416) = −.190, p <.001], though was found to be correlated with sex [ r (416) = −.572, p <.001].…”
Section: Methodsmentioning
confidence: 99%
“…In SPM, the TIV is calculated as the sum of the all intracranial tissues, with additional tissue class most introduced in the recent version of SPM 12 (e.g., external CSF as appose to part of the entire CSF classes in the early version) and regularized through wrapping the tissue segmentation with a manually corrected TIV mask (Keihaninejad et al, ) to improve the segmentation accuracy. The more rigorous definition of T1‐based TIV in SPM appears to be more consistent compared to FreeSurfer's scaling‐based estimation (Hansen et al, ; Keihaninejad et al, ; Sargolzaei et al, ; Sargolzaei et al, ; Sargolzaei et al, ), and is less affected by the brain atrophy (Pengas et al, ). However, both the FreeSurfer and the SPM8 automatic TIV estimation introduce systematic overestimation (Nordenskjold et al, ), which has been alleviated in SPM12 in which case a new method is introduced using template registration, which improves accuracy (Malone et al, ) and consistency (Heinen et al, ) of both TIV estimation, as well as brain volume measurements (Heinen et al, ; Vagberg et al, ).…”
Section: Discussionmentioning
confidence: 98%